Nickel-doped MoSe2 nanosheets with Ni–Se bond for alkaline electrocatalytic hydrogen evolution. (1st April 2020) - Yang, Yaqian; Zhao, Xu; Mao, Han; Ning, Rui; Zheng, Xiaohang; Sui, Jiehe; Cai, Wei
Abstract: Molybdenum diselenide (MoSe2 ) is a potential catalytic material for the electrocatalytic hydrogen evolution reaction (HER). However, due to the low density of its active sites, MoSe2 nanosheets feature high overpotential in HER, which limits its practical application. This describes the method of doping the Ni in MoSe2 nanosheets to increase active sites. The NiO2 evenly dispersed on MoSe2 by ethanol solution reduces to ~4 nm Ni nanoclusters under annealing process, which is firmly adhered to MoSe2 nanosheets with Ni–Se bond. The electrochemical active surface area of Ni-doped MoSe2 expands, proving that Ni dopants produce more activity sites in MoSe2 nanosheets. The overpotential of MoSe2 (at 10 mA cm −2 ) decreases from 335 mV to 181 mV with 4.5 at.% Ni doped in 1 M KOH. The Ni–MoSe2 also characterizes excellent stability for 12 h with the formation of Ni–Se bond. The study of doping Ni in MoSe2 nanosheets is of great guiding significance to the design and production of non-noble electrocatalysts for HER in alkaline media. Highlights: In synthesized process, ethanol makes Ni source evenly disperse in MoSe2 nanosheets. The Ni was doped in the inert planes of MoSe2, which increase active sites. The Ni was firmly adhered in MoSe2 nanosheets for the formation of Ni–Se bond.